2018
DOI: 10.1021/acs.jafc.7b04610
|View full text |Cite
|
Sign up to set email alerts
|

Constant Isothiocyanate-Release Potentials across Biofumigant Seeding Rates

Abstract: Biofumigation is an integrated pest-management method involving the mulching of a glucosinolate-containing cover crop into a field in order to generate toxic isothiocyanates (ITCs), which are effective soil-borne-pest-control compounds. Variation in biofumigation efficacy demonstrates a need to better understand the factors affecting pest-control outcomes and develop best practices for choosing biofumigants, growth conditions, and mulching methods that allow the greatest potential isothiocyanate release. We me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…However, it takes a long time to enable successful replanting if the rotation crops are not carefully selected . Many studies have found that some suitable rotation plants can alleviate root rot by directly inhibiting pathogen growth or enhancing the resistance of host plants by phytochemicals from root exudates or residue degradation. , Isothiocyanates (ITCs), the hydrolysis product of glucosinolates in Brassica plants, are considered to be good materials for alleviating soil-borne diseases. , For example, Brassica napus rotated with tobacco suppressed tobacco black shank caused by Phytophthora parasitica; the volatile ITCs could significantly inhibit the growth of root rot pathogens, such as Aphanomyces euteiches, Colletotrichum coccodes, Rhizoctonia solani, Helminthosporium solani. , Rotating Brassica with medicinal herbs or fumigating the diseased soil with ITCs may be an environmentally friendly method to alleviate root rot disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it takes a long time to enable successful replanting if the rotation crops are not carefully selected . Many studies have found that some suitable rotation plants can alleviate root rot by directly inhibiting pathogen growth or enhancing the resistance of host plants by phytochemicals from root exudates or residue degradation. , Isothiocyanates (ITCs), the hydrolysis product of glucosinolates in Brassica plants, are considered to be good materials for alleviating soil-borne diseases. , For example, Brassica napus rotated with tobacco suppressed tobacco black shank caused by Phytophthora parasitica; the volatile ITCs could significantly inhibit the growth of root rot pathogens, such as Aphanomyces euteiches, Colletotrichum coccodes, Rhizoctonia solani, Helminthosporium solani. , Rotating Brassica with medicinal herbs or fumigating the diseased soil with ITCs may be an environmentally friendly method to alleviate root rot disease.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Isothiocyanates (ITCs), the hydrolysis product of glucosinolates in Brassica plants, are considered to be good materials for alleviating soil-borne diseases. 11,12 For example, Brassica napus rotated with tobacco suppressed tobacco black shank caused by Phytophthora parasitica; 12 the volatile ITCs could significantly inhibit the growth of root rot pathogens, such as Aphanomyces euteiches, Colletotrichum coccodes, Rhizoctonia solani, Helminthosporium solani. 13,14 Rotating Brassica with medicinal herbs or fumigating the diseased soil with ITCs may be an environmentally friendly method to alleviate root rot disease.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The concentration and type of GSLs varied with different plant species and crop stages. 19,130 In many studies, 117,131 the flowering stage showed the highest concentration in different biofumigant crops. 130 Furthermore, in some Brassica plants, roots have a higher concentration of GSLs than other plant parts, and they subsequently have comparatively high antimicrobial activity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For the biofumigation treatment, the first crop of mustard was seeded on 16 June 2017 and 24 June 2019 at a seeding rate of 11.2 kg ha −1 according to seed company recommendation. The mustard plants were mowed and then immediately incorporated into the soil with disking on 20 July 2017 and 31 July 2019 at full flowering (i.e., approximately 50% flowers in main raceme open, older petals falling) for greatest biofumigation potential (Doheny-Adams et al, 2018 ; Saskatchewan mustard development commission., 2021 ). The second crop of mustard was seeded on 3 August 2017 and 6 August 2019 and mowed and immediately incorporated into the soil on 20 September 2017 and 14 September 2019 for additional biomass and biofumigation enhancement.…”
Section: Methodsmentioning
confidence: 99%